2021
DOI: 10.1099/mgen.0.000532
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome sequence analysis of Shigella from Malawi identifies fluoroquinolone resistance

Abstract: Increasing antimicrobial resistance and limited alternative treatments have led to fluoroquinolone-resistant Shigella strain inclusion on the WHO global priority pathogens list. In this study we characterized multiple Shigella isolates from Malawi with whole genome sequence analysis, identifying the acquirable fluoroquinolone resistance … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Antimicrobial resistance testing was performed using a panel of 20 antibiotics; all Shigella isolates were resistant to trimethoprim-sulfamethoxazole and ampicillin but susceptible to the other antibiotics tested [ 13 ]. More recently, however, whole genome sequencing of Shigella isolates from invasive infection in Malawi has identified the emergence of fluoroquinolone resistance [ 14 ]…”
Section: Historical Shigella Incidence Prevalence ...mentioning
confidence: 99%
“…Antimicrobial resistance testing was performed using a panel of 20 antibiotics; all Shigella isolates were resistant to trimethoprim-sulfamethoxazole and ampicillin but susceptible to the other antibiotics tested [ 13 ]. More recently, however, whole genome sequencing of Shigella isolates from invasive infection in Malawi has identified the emergence of fluoroquinolone resistance [ 14 ]…”
Section: Historical Shigella Incidence Prevalence ...mentioning
confidence: 99%
“…There is variation in shigellosis incidence, sub-continentally and nationally, with national attributable disease burden estimates of up to 63.3% of diarrhoeal cases, and intra-national variation as high as 34% [46,47]. The available data show AMR Shigella are present across the entire sub-continent, and MDR, where reported, is more common in S. flexneri [31,46,[48][49][50]. South Africa has a high incidence (2.7 hospitalisations/100,000 persons per year) of shigellosis, caused predominantly by S. flexneri and S. sonnei, discovered through routine, national shigellosis surveillance, enabling detailed examination of the national epidemiology of serotypes from both globally important serogroups within sub-Saharan Africa [51][52][53][54][55][56][57][58].In this study, we use WGSA to examine the epidemiology, ecology, and accessory genome dynamics of shigellosis in the sub-Saharan nation of South Africa using isolates collected as part of the national surveillance between 2011 and 2015.…”
mentioning
confidence: 97%
“…Further WGSA of the GEMS study isolates showed multiple Phylogroups of S. flexneri in each participating African country, highlighting the diversity of circulating strains [16]. While this provides a useful snapshot into the diversity of Shigella strains circulating regionally, detailed national studies are needed to further unpick the ecology of shigellosis in the region.Non-genomic studies from across sub-Saharan Africa highlight the importance of endemic disease in the region and confirm S. flexneri is typically the dominant serogroup of Shigella [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45]. There is variation in shigellosis incidence, sub-continentally and nationally, with national attributable disease burden estimates of up to 63.3% of diarrhoeal cases, and intra-national variation as high as 34% [46,47].…”
mentioning
confidence: 99%
See 1 more Smart Citation